Systematic Literature Review: Analisis Kemampuan Berpikir Komputasional Siswa Sekolah Dasar Menggunakan Scratch - Siti Zia Hadatul Hasanah; Yahfizham Yahfizham (LPPM Politeknik Pratama, 2024)
The increasing need for the use of technology in all sectors, especially in the education sector, is the formation of student-oriented learning. This provides new challenges in the 21st century which now require students to mature not only in science and simple thought processes but also the ability to create and develop what is needed in the 21st century. The Ministry of Education, Culture, Research and Technology declares that participants Students must have Computational Skills (CT). To obtain problem-solving skills, students should emphasize computational learning in elementary schools so that students are able to face existing challenges and have computational skills from an early age. One technology that is suitable for application in elementary school learning is Scratch, a programming application designed specifically for beginners, especially children. The author's aim in conducting this research was to analyze the computational abilities of elementary school students using Scarch. The method the author uses is the Review Literature Study method, by reviewing previous journals related to the topic the author discusses.